2020
DOI: 10.30651/else.v4i1.4379
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Teknologi Augmented Reality pada Media Pembelajaran Bahasa Arab: Durus Al-Lughah Jilid 1

Abstract: Abstrak: Saat ini penggunaan teknologi telah banyak dikembangkan sebagai media pembelajaran diberbagai lembaga pendidikan. Sebagai Universitas berbasis pesantren yang sehari-hari menggunakan Bahasa Arab, Universitas Darussalam Gontor (UNIDA Gontor) telah memiliki media pembelajaran baik dalam bentuk buku bahasa arab (Durusullughah Al-Arabiyah), dan dalam bentuk aplikasi, diantaranya aplikasi android menggunakan metode terjemahan (bit.ly/tamrinlughah) dan metode langsung (http://bit.ly/duruslughah). Seiring ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…However, the method is broader, emphasising social interaction (Hasan, 2020). The use of AR multimedia technology improves student performance, motivation, and satisfaction in the Third Language Learning Method (Fauzan et al, 2020;Marin-Diaz et al, 2022)…”
Section: Methods Of Instruction In Third Language Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the method is broader, emphasising social interaction (Hasan, 2020). The use of AR multimedia technology improves student performance, motivation, and satisfaction in the Third Language Learning Method (Fauzan et al, 2020;Marin-Diaz et al, 2022)…”
Section: Methods Of Instruction In Third Language Subjectsmentioning
confidence: 99%
“…Despite having a positive impact, third-language effectiveness remains far behind (Akashah et al, 2016). AR technology can be used in games (Sepasgozar, 2020), language translation, vocabulary, sentence reading, and correct pronunciation (Alrige et al, 2021;Cahyani et al, 2021;Fauzan et al, 2020;Lubis et al, 2019). Thus, augmented reality (AR) is a new system that is rapidly expanding and has the potential to improve the effectiveness of teaching and learning in order to meet educational technology goals in the future (Alrige et al, 2020).…”
Section: The Impact Of Augmented Reality On Student Performancementioning
confidence: 99%
“…Another study by [29] titled "The Application of Augmented Reality Technology in Arabic Language Learning Media: Durus Al-Lughah Volume 1" stated that an application related to augmented reality technology was developed for learning Arabic language at Universitas Darussalam Gontor (UNIDA). The application uses the Android platform and is developed in software, such as Blender 3D, Corel Draw, and Unity 3D.…”
Section: B Related Workmentioning
confidence: 99%
“…Attention to Focus on a Topic being Taught Findings show that the augmented reality technology application is not only able to attract the attention of teachers involved in the study but also prove that the augmented reality technology is able to attract the attention of students to focus on a topic being taught and the students' curiosity in the lessons being studied [11,29]. This statement is supported by the study [33] who found that students, especially children are very interested in using mobile phones in order to learn something new which is often used by them in their daily lives.…”
Section: Augmented Reality Technology Is Able To Attract Students'mentioning
confidence: 99%
“…Salah satu contoh pemanfaatan ponsel pintar di bidang Pendidikan bisa kita manfaatan untuk menjadi media pembelajaran, menurut Kamus Besar Bahasa Indonesia (KBBI) media berarti perantara, penghubung; alat (sarana) komunikasi seperti koran, majalah, radio, televisi, film, poster, dan spanduk, yang terletak diantara dua pihak (orang, golongan, dan sebagainya) dalam (KBBI Kemdikbud, 2019). Salah satu media pembelajaran yang dapat digunakan serta dikembangkan pada sistem pendidikan berbasis teknologi saat ini adalah augmented reality (Fauzan et al, 2020 (Hakim, 2018).…”
Section: Pendahuluanunclassified